COHERENCE SCORES AND COHERENCE LEVEL: MODIFICATION EFFECTS OF HYDRO-AROMATHERAPY AND MINDFULNESS MEDITATION ON PATIENTS SUFFERING FROM INFLAMMATORY RHEUMATIC DISEASES - Slavić, Vjeroslava (Acta medicae Medianae, 2022)
Background: Recently, heart rate variability (HRV) and coherence score (CS) or coherent heart rhythm pattern are validated method to establish autonomic nervous system (ANS) activity.The aim of this research is to assess the modifications of CSs in a sample of patients suffering from inflammatory rheumatoid diseases during their physical treatment and rehabilitation based on natural factors as well as hydro-aromatherapy and meditation.Materials and methods: This study included 44 Norwegian patients with confirmed diagnosis of inflammatory rheumatoid diseases during four weeks of physical treatment and rehabilitation at the Institute “Dr Simo Milosevic” Igalo, Montenegro. They were divided into two groups: (1) experimental (n = 22) and (2) control (n = 22). All the patients received the standard protocol based on natural healing mud and mineral water. However, the patients in the experimental group had additional hydro-aromatherapy (mineral water enriched with essential oils of Lavender, Orange and Lemon) and meditation. The emWave Pro machine measures CS before and after treatment. There were three coherence levels (CL): low, medium and high. Low reflected the amount of time in which there was no wavelike activity, medium some wavelike activity, and high a considerable amount of wavelike activity in the HRV tracing.Results: After treatment, the CS was found to be significantly higher in the experimental group than in the control group (p < 0.015). Simultaneously, the high CL was significantly higher in the experimental group (p < 0.026), and the low CL was significantly lower in the control group (p < 0.017). Comparison of the obtained CLs between the experimental and control groups after treatment only the medium CL was statistically different (p < 0.009).Conclusion: The standard protocol in the Institute Igalo with the addition of hydro-aromatherapy and meditation significantly improved the ANS activity of patients suffering from inflammatory rheumatoid diseases.
Keywords: Coherence score, Coherence levels, Inflammatory rheumatoid diseases